A Broadband High-Efficiency Hybrid Continuous Inverse Power Amplifier Based on Extended Admittance Space - Ni, Chun; Wang, Hui; Liu, Jing; Chen, Mingsheng; Zhang, Zhongxiang; Zhang, Liang; Zhu, Jiabing; Wu, Xianliang (Frontiers in Physics, 2021)
A novel hybrid continuous inverse power amplifier (PA) that constituted by a continuum of PA modes from the continuous inverse Class-F to the continuous inverse Class-B/J is proposed, and a detailed mathematical analysis is presented. The fundamental and second harmonic admittance space of the hybrid PA proposed in this paper are analyzed mathematically. By introducing phase shift parameter into the current waveform formula of hybrid continuous inverse PA, the design space of fundamental and second harmonic admittance is expanded, further increasing the operating bandwidth. The efficiency of the amplifier under different parameter conditions is calculated. In order to verify this method, a broadband high efficient PA is designed and fabricated. The drain voltage and current waveforms of the amplifier are extracted for analysis. The experimental measured results show a 60.7%-71.5% drain efficiency across the frequency band of 0.5-2.5 GHz (133% bandwidth), and the designed PA can obtain a 11.8 dB-13.9 dB gain in the interesting frequency range. Measured results are confirmed to be in good agreement with theory and simulations.